Tumour stem cells in schwannoma: A review. (April 2019) - Cutfield, Samuel W.; Wickremesekera, Agadha C.; Mantamadiotis, Theo; Kaye, Andrew H.; Tan, Swee T.; Stylli, Stanley S.; Itineang, Tinte
Highlights: Evidence of the presence of tumour stem cells (TSCs) in benign tumours is increasing. Schwannoma expresses embryonic stem cell markers OCT4, SOX2, NANOG and c-MYC. Progenitor cell markers CD133 and CD44 have also been demonstrated in schwannoma. Characterisation of TSCs in schwannoma may improve understanding of its biology. Abstract: Schwannoma is a peripheral nerve tumour, accounting for 5% of benign soft tissue tumours, with vestibular schwannoma comprising 6% of all intracranial tumours. The tumour stem cell concept is rapidly gaining traction underscoring the understanding of tumourigenesis. It proposes a small subpopulation of primitive cells as the origin of the tumour and these cells account for treatment resistance, local recurrence and distant metastasis in malignant tumours. This review outlines the stem cell markers used to identify and characterise stem cells and progenitor cells in tumours and examines current evidence of the presence of tumour stem cells in schwannoma.